Effect of energy and protein supplementation on growth and nutrient requirement estimation in crossbred bull calf (Bangladesh Journal of Animal Science, 2018)
This study was carried out to investigate the effects of supplying different levels of energy and protein on the growth performance and nutrient requirements estimation in crossbred bull calves. Feeding trial was conducted for 60 days with 12 numbers of crossbred bull calves. The animals were divided into four groups i.e. T0, T1, T2and T3. Four levels of metabolizable energy (ME) and digestible crude protein (DCP) were supplied respectively in four dietary groups, T0=17.4 MJ/d and 85 g/d as maintenance ration, T1=19.22 MJ/d and 188 g/d for 200 g/d targeted BWG, T2=21.29 MJ/d and 243 g/d for 400g/d targeted BWG, T3=23.37 MJ/d and 255 g/d for 600g/d targeted BWG. A positively correlation of BWG with uptake of nutrients (energy and protein) and feed conversion efficiency of different dietary groups was observed. Results revealed that the average daily body weight gain (BWG) in T1 (200 g/d) fulfills against the targeted BWG 200 g/d, T2 maintaining BWG 327 g/d against the targeted BWG 400 g/d and T3 maintaining BWG 422 g/d against the targeted BWG 600 g/d. Considering the growth response of crossbred bull calves it is evident that T1 is better than other dietary groups. Again, estimated ME requirement for maintenance was 16.14 MJ/d and for each kg BWG/d requires ME was 14.69 MJ for 100 kg body weight of crossbred bull calves. The maintenance requirement of DCP was 60.65 g/d and for each kg BWG/d requires DCP was 0.56 g for 100 kg body weight of crossbred bull calves.Bang. J. Anim. Sci. 2017. 46 (3): 179-187